Structural change and deindustrialization at the northern border of Mexico - Martínez Sidóna, Gilberto; Barajas Ramos, Alejandrina; Corrales, Salvador (My University, 2022)
This research aims to analyze the manufacturing industry of the northern border of Mexico to identify its development trends in the period of 1999 to 2019. It is hypothesized that its performance has been of high specialization, which makes the presence of deindustrialization as a pattern of structural change difficult. To reach the objective and test the hypothesis, a structural change index, a specialization coefficient and a model with panel data was calculated to analyze the determinants of the specialization coefficient. The results suggest that there is no process of deindustrialization on the northern border, due to the high specialization in manufacturing that is explained by variables that favor manufacturing such as the gdp of the United States, the real exchange rate, investment and the employed population.
Estudios Fronterizos
Keywords: Structural change; Deindustrialization; Northern border of Mexico; Specialization coefficient; Manufacturing industry; Campus Mexicali